What does phenomenology contribute to the nurse-patient relationship? - Luis Cibanal Juan; María del Carmen Arce Sánchez (Universidad de Alicante, 1997)
The pre-supposed philosophical basis for the nurse-patient relationship is considered in the present article. The relationship between a nurse and a patient, as has been generally established, is seen from a humanistic and phenomenological perspective. Our study, based on Husserl's point of view - besides that of the French existentialist movement - confirms our main point: the patient should be considered from an holistic approach.